Pemanfaatan Kombinasi Limbah Fly Ash dan Bottom Ash Dalam Campuran Mortar Untuk Paving Block - khairizal, Yuri; Ibrahim, Ibrahim; Fikri, Julian; Wiranata, Didi Yuda; Amanah, Tody; Mahmuda, Mahmuda; Sumiati, Sumiati (Universitas Batanghari Jambi, 2024)
Various alternative solutions to reduce waste continue to be sought and developed. This includes fly ash and bottom ash which are waste products from burning coal, one of which is produced by Steam Power Plants (PLTU). So the increasing need for electricity will also be followed by an increase in the amount of waste. This type of waste is utilized in various fields of science, such as agriculture, industry and quite a lot in the construction sector. As a field that continues to develop along with people's need to live and move, utilization in the construction sector has great potential as a solution to reduce this waste. The use of fly ash and bottom ash in construction material mixtures as a quality enhancer or simply to reduce the use of natural materials continues to be carried out. This research will focus on the utilization of waste at a large percentage on a construction product scale. Substitution in the composition of the mortar mixture which is the initial product shows the effect of improving quality at a relatively low percentage in the variations used in this research. However, the full substitution of this waste as a substitute for natural materials, namely fine aggregate, is still in a fairly good range, especially in the composition of mortar mixtures with relatively low quality targets or in composition ratios with more aggregate material than cement or binder.